2017
DOI: 10.7494/geol.2017.43.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and geotechnical properties of an ash-slag mixture deposited on a landfill in terms of its use in engineering

Abstract: Coal combustion ash-slag mixtures have been deposited in landfills in Poland for decades. At the same time, there is a shortfall in the amount of available materials related to the construction and modernisation of transportation infrastructure. Thus, a typical landfill of a power station was chosen and the aim of the study was to assess the suitability of an ash-slag landfill mixture for construction engineering purposes. The following physicochemical analyses were conducted: pH, specific electrical conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Research by Reddy et al [32] showed that the permeability coefficient of the power plant bottom ash had values similar to those obtained in this study from 1.34 × 10 −6 to 2.01 × 10 −6 m/s; hence, such waste ash can be effectively used as road embankment construction material. In contrast, Szwalec et al [18] give a wide range of permeability coefficient values for coal waste ash ranging from 3.4 × 10 −11 to 2.61 × 10 −2 m/s. Low water permeability coefficients (from 1.16 × 10 −5 to 1.27 × 10 −5 m/s) obtained by Lange et al [19] were explained by the chemical composition of the bottom ashes and slags containing large amounts of The average values of permeability k ranged from 4.4 × 10 −7 to 1.91 × 10 −6 m/s.…”
Section: Permeability Measurementsmentioning
confidence: 93%
See 2 more Smart Citations
“…Research by Reddy et al [32] showed that the permeability coefficient of the power plant bottom ash had values similar to those obtained in this study from 1.34 × 10 −6 to 2.01 × 10 −6 m/s; hence, such waste ash can be effectively used as road embankment construction material. In contrast, Szwalec et al [18] give a wide range of permeability coefficient values for coal waste ash ranging from 3.4 × 10 −11 to 2.61 × 10 −2 m/s. Low water permeability coefficients (from 1.16 × 10 −5 to 1.27 × 10 −5 m/s) obtained by Lange et al [19] were explained by the chemical composition of the bottom ashes and slags containing large amounts of The average values of permeability k ranged from 4.4 × 10 −7 to 1.91 × 10 −6 m/s.…”
Section: Permeability Measurementsmentioning
confidence: 93%
“…The permeability coefficient measurements were performed with a constant hydraulic gradient as well as with a constant flow [30]. The tests consisted of determining the amount of water that will filter through a soil sample with a cross-section A in time t at the hydraulic gradient i and at the determined water temperature [10,[17][18][19][20][21][22][23][24][25][26][27][28][29]. The hydraulic gradient i was calculated according to the following formula [30]:…”
Section: Measurement Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the evaluation methods is the analysis of the aqueous extract obtained in the leaching test. Research into energy waste has shown that the content of heavy metal cations in aqueous extracts is low, which proves that they create forms that are insoluble or sparingly soluble in water (Mazurkiewicz 1990;Mazurkiewicz et al 1997;kapuściński and Strzałkowska 2005;Szwalec et al 2017). However, it should be noted that the standard aqueous extract completely ignores the issues of waste kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that the standard aqueous extract completely ignores the issues of waste kinetics. Some waste releases toxic substances only after some time or under specific conditions (kapuściński and Strzałkowska 2005;Szwalec et al 2017;Dudas 1981). An important role in the leaching of fly ash is played by the way in which a given element is present in coal (Izquierdo and Querol 2012).…”
Section: Introductionmentioning
confidence: 99%